Pedagogy and public-funded research: an exploratory study of skills in digital humanities projects. Issue 3 (13th May 2019) - Garwood, Deborah A.; Poole, Alex H.
Abstract : Purpose: Public-funded research in digital humanities (DH) enhances institutional and individual research missions and contributes open data to a growing base of globally networked knowledge. The Digging into Data 3 challenge (DID3) (2014–2016) is an international, interdisciplinary and collaborative grant initiative, and the purpose of this paper is to explore skills that faculty and students brought to projects and others they acquired and shared on collaborative teams. Design/methodology/approach: Rooted in the naturalistic paradigm, this qualitative case study centers on semi-structured interviews with 53 participants on 11 of the 14 DID3 projects. Documentary evidence complements empirical evidence; analysis is constructivist and grounded. Findings: Hailing from diverse academic research institutions, centers and repositories, participants brought 20 types of discipline-based or interdisciplinary expertise to DID3 projects. But they reported acquiring or refining 27 other skills during their project work. While most are data-related, complementary programming, management and analytical skills push disciplinary expertise toward new frontiers. Project-based learning and pedagogy function symbiotically; participants therefore advocate for aligning problem-solving skills with pedagogical objectives at home institutions to prepare for public-funded DH projects. A modified content analysis juxtaposes DID3 skills with those advanced in 23 recent DH syllabi to identify commonalities and gaps. Originality/value: Pedagogy has an important yet under-researched and underdeveloped role in public-funded DH research.